Solar noble gases in an iron meteorite indicate terrestrial mantle signatures derive from Earth’s core - Vogt, Manfred; Trieloff, Mario; Ott, Uli; Hopp, Jens; Schwarz, Winfried H. (Communications earth & environment, 2021)
Noble gases are important tracers of planetary accretion and acquisition of volatiles to planetary atmospheres and interiors. Earth’s mantle hosts solar-type helium and neon for which 20Ne/22Ne ratios advocate either incorporation of solar wind irradiated solids or solar nebula gas dissolution into an early magma ocean. However, the exact source location of primordial signatures remains unclear. Here we use high-resolution stepwise heating gas extraction experiments to analyse interior samples of the iron meteorite Washington County and find that they contain striking excesses of solar helium and neon. We infer that the Washington County protolith was irradiated by solar wind and that implanted noble gases were partitioned into segregating metal melts. The corollary that solar signatures are able to enter the cores of differentiated planetesimals and protoplanets validates hypotheses that Earth’s core may have incorporated solar noble gases and may be contributing to the solar signatures observed in Earth’s mantle.